Polemik Ulama Nusantara: Narasi Faktual Tentang Kebebasan Berpendapat - Ahmad Fauzi Ilyas; Radinal Mukhtar Harahap (Jurnal Penelitian Medan Agama, 2019)
This article seeks to put polemic-polemic that has occurred in the Indonesian scholars related to the problems that develop in the archipelago itself, especially the problem of Islamic law. Through the assessment of the works that they write directly (library research), it is found that the Ulama Nusantara is a figure who uphold the principle that they believe and not antipathy – in the sense of closing oneself to the existence of the Ulama Other Malay-based and different Indonesian archipelago. The attitude is drawn from some polemic that has occurred, among which are related to Nafune and Kentongan, stood when the Prophet's Mawlid warning, concerning the order of Naqsyabandiyah, surrounding the air-ushalli, preaching of Indonesian language, and inheritance especially in Minangkabau region. The narrative-narrative found, for the present context, can be used to understand how the scientific climate is affected in the concept of freedom of opinion has been preconceived and it is very influential in realizing the culture of science that becomes The key to the establishment of Islamic civilization Nusantara now. The task of scientists and experts today to continue